Laporan Analisa Manajemen Proyek pada Usaha “The Heat Packz” - Phangestu, Steffany Jessica; Edison, Edison; Andrian, Salsabila Syifa (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Based on the business report “The Heat Packz”, it can be concluded that the “The Heat Packz” project has succeeded by implementing established project management principles. This success is evident from the application of strict quality management, where each production stage is monitored to ensure the product meets set standards. Additionally, the use of the RACI matrix has clarified team members' roles and responsibilities, ensuring tasks are completed efficiently and on time. The project also demonstrated effectiveness in communication strategy and risk management. By developing and implementing an effective communication plan, all stakeholders received necessary information promptly. Good risk management, including risk identification and mitigation, ensured the project ran smoothly without significant obstacles. Furthermore, efficient inventory planning and stakeholder relationship management supported stable operations and met consumer expectations, contributing to the overall success of the project. Keywords: Communication Strategy, Project Management, Quality Management, RACI Matrix, Risk Management